Fic Proteins Inhibit the Activity of Topoisomerase IV by AMPylation in Diverse Bacteria - Lu, Can-Hua; McCloskey, Alix; Chen, Fu-Rong; Nakayasu, Ernesto S.; Zhang, Li-Qun; Luo, Zhao-Qing (Frontiers in Microbiology, 2020)
The Fic (filamentation induced by cyclic AMP) domain is a widely distributed motif with a conserved sequence of HPFx[D/E]GN[G/K]R, some of which regulate cellular activity by catalyzing the transfer of the AMP moiety from ATP to protein substrates. Some Fic proteins, including Fic-1 from the soil bacterium Pseudomonas fluorescens strain 2P24, have been shown to inhibit bacterial DNA replication by AMPylating the subunit B of DNA gyrase (GyrB), but the biochemical activity and cellular target of most Fic proteins remain unknown. Here, we report that Fic-2, which is another Fic protein from strain 2P24 and Fic-1 AMPylate the topoisomerase IV ParE at Tyr109. We also examined Fic proteins from several phylogenetically diverse bacteria and found that those from Yersinia pseudotuberculosis and Staphylococcus aureus AMPylate ParE and GrlB, the counterpart of ParE in Gram-positive bacteria, respectively. Modification by Fic-1 of P. fluorescens and FicY of Y. pseudotuberculosis inhibits the relaxation activity of topoisomerase IV. Consistent with the inhibition of ParE activity, ectopic expression of these Fic proteins causes cell filamentation akin to the canonical par phenotype in which nucleoids are assembled in the center of elongated cells, a process accompanied by the induction of the SOS response. Our results establish that Fic proteins from diverse bacterial species regulate chromosome division and cell separation in bacteria by targeting ParE.